PENDEKATAN STUDI ISLAM DI PERGURUAN TINGGI ISLAM - Apri Kurniasih (LPPM STAI DARUSSALAM LAMPUNG, 2012)
The style of Islamic studies at the Islamic higher education, namely: a varietyof Islamic studies is no longer bound or tend to side with one particularmadhhab; patterned Majlisi, the privilege of this orientation is a priorityto uniformity and stability of the people; patterned campus, characteristicfeature of this orientation is the campus life characterized by the dominanceof independent thinking; campus pattern to be developed in the Islamichigher education so that students can be more active in expressing theiropinion; Islamic studies at the Islamic College coupled with the introductionof modern sciences, both social sciences and natural sciences.Character of Islamic studies at the Islamic higher education is more orientedtoward mastery of the material substance and possession of the treasures ofIslamic scholarship, which will then be followed by practice of the teachingsof Islam which has learned. While the nature of Islamic studies in the West ismore oriented to Islam as a social reality or fenmena only. The methodologyused in the study of Islam at Islamic higher education, among others, byusing a normative approach, sociological, historical, philosophical, andempirical.